Activation of angiotensin-converting enzyme 2 produces an antidepressant-like effect via MAS receptors in mice - Osamu Nakagawasai; Kohei Takahashi; Taisei Koyama; Ryota Yamagata; Wataru Nemoto; Koichi Tan-No (Molecular Brain, 2023)
Abstract Angiotensin (Ang)-converting-enzyme (ACE) 2 converts Ang II into Ang (1–7), which in turn acts on MAS receptors (ACE2/Ang (1–7)/MAS receptors pathway). This pathway has neuroprotective properties, making it a potential therapeutic target for psychiatric disorders such as depression. Thus, we examined the effects of diminazene aceturate (DIZE), an ACE2 activator, on depressive-like behavior using behavioral, pharmacological, and biochemical assays. To determine whether DIZE or Ang (1–7) produce antidepressant-like effects, we measured the duration of immobility of mice in the tail suspension test following their intracerebroventricular administration. Next, we measured the levels of ACE2 activation in the cerebral cortex, prefrontal cortex, hippocampus, and amygdala after DIZE injection, and examined which cell types, including neurons, microglia, and astrocytes, express ACE2 in the hippocampus using immunofluorescence. Administration of DIZE or Ang (1–7) significantly shortened the duration of immobility time in the tail suspension test, while this effect was inhibited by the co-administration of the MAS receptor antagonist A779. DIZE activated ACE2 in the hippocampus. ACE2 was localized to neurons, astrocytes, and microglia in the hippocampus. In conclusion, these results suggest that DIZE may act on ACE2-positive cells in the hippocampus where it increases the activity of ACE2, thereby enhancing signaling of the ACE2/Ang (1–7)/MAS receptor pathway and resulting in antidepressant-like effects.